Transhumanism and the image of God : today's technology and the future of Christian discipleship - Shatzer, Jacob, 1986- (IVP Academic, an imprint of InterVarsity Press, 2019)
Examining the transhumanist movement, biblical ethicist Jacob Shatzer grapples with the potential for technology to transform the way we think about what it means to be human. Exploring the doctrine of incarnation and topics such as artificial intelligence, robotics, medical technology, and communications tools, he guides us into careful consideration of the future of Christian discipleship in a disruptive technological environment.